Relations for Einstein–Yang–Mills amplitudes from the CHY representation - Leonardo de la Cruz; Alexander Kniss; Stefan Weinzierl (Physics Letters B, 2017)
We show that a recently discovered relation, which expresses tree-level single trace Einstein–Yang–Mills amplitudes with one graviton and (n−1) gauge bosons as a linear combination of pure Yang–Mills tree amplitudes with n gauge bosons, can be derived from the CHY representation. In addition we show that there is a generalisation, which expresses tree-level single trace Einstein–Yang–Mills amplitudes with r gravitons and (n−r) gauge bosons as a linear combination of pure Yang–Mills tree amplitudes with n gauge bosons. We present a general formula for this case.